The Effect of Using Connecting, Organizing, Reflecting, Extending (CORE) Model on Students’ Vocabulary Mastery at the Seventh Grade of SMP Negeri 9 Padangsidimpuan in 2024/2025 Academic year - Kamisah, Kamisah; Sipahutar, Rodia; Roito, Amelia; Etelinda, Fanny; Erdana, Yogi (ITScience (Information Technology and Science), 2026)
The aims of this research are to know the application of the CORE model in teaching vocabulary mastery, the students' vocabulary mastery before and after using the CORE model, and whether there is any significant effect of using the CORE model on students' vocabulary mastery at the seventh grade of SMP Negeri 9 Padangsidimpuan. This research uses an experimental method with a pre-experimental design by a one-group pretest-posttest design. The population of this research is all of the seventh-grade students of SMP Negeri 9, which consists of 168 students. Sample is the seventh 1 which consists of 28 students, who were taken by purposive sampling. In data collection techniques, researchers use observation sheets and tests as an instrument. The results of this research: the application of the core model is 80% (very good category). The students’ vocabulary mastery before and after using the CORE model is 46.14 (poor category) and 78.57 (good category). The hypothesis testing researcher shows the Asymp. Sig. (2-tailed) The value was 0.000, lower than the significance level of 0.05 (0.000 < 0.05). So the hypothesis is accepted. It means that there is a significant effect of the connecting, organizing, reflecting, and extending (CORE) model on the vocabulary mastery of the seventh-grade students of SMP Negeri 9 Padangsidimpuan in the 2024/2025 Academic Year.